The biological relationship among depression, vitamins B9, B12, and D, and genetic variants: a systematic review - Soriano-Gonzalez, Rosella; Ramirez-Olea, Hugo; Gonzalez-Soltero, Rocio; Chavez-Santoscoy, Rocio Alejandra (Frontiers in Nutrition, 2025)
Background and aimsDepression is a leading cause of disability worldwide; studies have described it as a multifactorial disease that involves biological, psychological, and environmental factors. This systematic review explores the role of vitamins B9, B12, and D in depression, particularly emphasizing their biological effects, genetic variant interactions, and potential treatment implications.MethodsA systematic literature review was conducted in Web of Science (WOS) and PubMed up to 15th June 2025. This review included 24 studies from randomized controlled trials (RCTs), observational studies, and case reports and examined the associations between genetic variants involved in vitamins B9, B12, and D metabolism; their biological processes; and outcomes in depression. Following the PRISMA criteria, researchers analyzed and extracted data independently; this resulted in the inclusion of 24 eligible papers (14 of vitamins B9 and B12 and 10 of vitamin D).ResultsStudies varied widely in design and methodology. Deficiencies in vitamins B9 (folate) and B12 (cobalamin) are associated with decreased neurotransmitter biosynthesis, higher homocysteine levels, and increased depressive symptoms. Vitamin D deficiency has also been associated with mood regulation through its effects on neurotransmission. Genetic variants, particularly in the MTHFR gene, have been associated with significant influence on individual susceptibility to depression in some populations, highlighting the interaction between genetics and micronutrient bioavailability and the need for further studies with diverse populations, larger study samples, and the inclusion of more genetic variants.ConclusionThis systematic review emphasizes the role of vitamins B9, B12, and D and genetic variants associated with the development of depression. Regardless of the encouraging findings that supplementation with vitamins B9, B12, and D could support depressive symptomatology, additional research is needed to propose therapeutic guidelines. Personalized strategies considering dietary, genetic and environmental factors could enhance treatment results for individuals with depression.